Hubungan Pengetahuan dan Dukungan Keluarga dengan Rendahnya Kunjungan Lansia Keposyandu Lansia di Wilayah Kerja Puskesmas Marunggi - Yesi Maifita; Miftakhul Zanah; Asmiati (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2023)
Elderly Posyandu is a forum for communication, technology transfer, and health services by the community and for the community which has strategic value for the development of human resources, especially the elderly. Knowledge and family support play a very important role in encouraging the interest or willingness of the elderly to participate in elderly Posyandu activities. The purpose of this study was to determine the relationship between knowledge and family support with the low number of visits by the elderly to the elderly Posyandu in the Working Area of ​​the Talu Health Center in 2020. The research was conducted in April 2020. This type of research was a descriptive analytic study with a cross sectional design. The population in this study were all elderly people aged 60 to > 70 years in the work area of ​​the Talu Public Health Center, using the accidental sampling technique to obtain a sample of 30 elderly people. Data were analyzed univariately and bivariately using a computerized statistical test using SPSS Ver.17 with a significance limit of α = 0.05 and a 95% degree of confidence. The results of the univariate analysis showed that 46.7% of the elderly had low knowledge, 53.3% had good family support for the elderly and 60% visited the elderly Posyandu for the elderly. Bivariate analysis found a p value (p<0.05) meaning that there was a significant relationship between knowledge (p=0.021) and attitude (p=0.004) with visits to the elderly posyandu in the Talu Health Center area in 2020. The results of this study can be concluded that it turns out that there is a relationship between knowledge and family support with visits to the elderly posyandu. It is hoped that the role of health workers will be more active in making visits to the elderly in people's homes to find out health conditions and free treatment for the elderly and not be stuck in the activities of the elderly Posyandu.